Expression of cancer stem cell markers in metastatic melanoma to the brain. (February 2019) - Wickremesekera, Agadha C.; Brasch, Helen D.; Lee, Valerie M.; Davis, Paul F.; Woon, Kelvin; Johnson, Reuben; Tan, Swee T.; Itinteang, Tinte
Highlights: Metastatic melanoma to the brain expresses embryonic stem cell markers. There may be three cancer stem cell subpopulations within metastatic melanoma to the brain. These cancer stem cells within metastatic melanoma to the brain may be a novel therapeutic target. Abstract: We have recently characterized cancer stem cell (CSC) subpopulations in different types of cancer. This study aimed to identify and characterize CSCs within metastatic melanoma (MM) to the brain. 3, 3-diaminobenzidine (DAB) immunohistochemical (IHC) staining of ten samples of MM to the brain demonstrated the expression of the embryonic stem cell (ESC) markers OCT4, NANOG, SALL4, SOX2 and pSTAT3. Protein expression of all five ESC markers except SALL4 were confirmed by Western blotting on five samples and transcriptional activation of all five markers was demonstrated using NanoString mRNA analysis on four samples. Immunofluorescence IHC staining suggested the presence of CSCs that stained for OCT4, SALL4, SOX2 or NANOG. Some of these cells also stained for Melan-A. Also, a pSTAT3 + /CD34 + primitive subpopulation was detected on the endothelium of microvessels. These CSCs may be a novel therapeutic target for MM to the brain.